Changing Time – Shaping World : Changemakers in Arts & Education - Anna Maria Loffredo; Rainer Wenrich; Charlotte Axelsson; Wanja Kröger (transcript, 2022)
A World of Changemakers – how can a hybrid arts lecture series concept in e-learning create attitudes and shape skills as a playful and critical thinking navigator in an uncertain world? To re-create meaning is an interdisciplinary cross-sectional task of our zeitgeist in a civil society. The international contributors represent key roles in relevant philosophical, technical or economic debates, non-university community art & design projects or companies.